A case study: the effective of marketing strategic for TM home prepaid product from Telekom Malaysia Company / Amie Adlina Azizan - Azizan, Amie Adlina (Faculty of Business and Management, 2009)
The case is based on the company have the implementation to promote Telekom Malaysia Home Prepaid which can attract customer to use the product. TMHP is the core product for consumer category of the product and Telekom Malaysia have created new product for TMHP. TMHP is focus on low ECP which that have more cable to encourage their new customer who not installed the fixed line. Telekom Malaysia had doing their research before they had promoted to the new customer. The purposes are to identify the problem, analysis, exploration the strategic to promote their customer. Telekom Malaysia need to make this project will worked for the successful to accomplish their target market.